Numerical and Experimental Investigations on Hydrodynamic Performance of a Newly Designed Deep Bottom Trawl - Guan, Qinglong; Zhu, Wenbin; Zhou, Aizhong; Wang, Yongjin; Tang, Weiyao; Wan, Rong (Frontiers in Marine Science, 2022)
Better design and understanding of hydrodynamic performance of fishing gear are crucial to improving fishing efficiency. In this paper, a new bottom trawl was designed based on target fishing vessel for deep–water fishing ground. The hydrodynamic performance of the deep bottom trawl was investigated by means of numerical simulation and physical model test. A numerical model of the trawl system was established based on the finite element method. The principle of minimum potential energy was applied to determine the equilibrium configuration and the tension distribution of the trawl in uniform current. The Newton–Raphson method was employed to solve the nonlinear equilibrium equation. A series of physical model tests were conducted in a towing tank to verify the accuracy of the numerical method. The results showed that the working towing speed of the trawl was 3.5 kn. At that speed, the drag force was 50 kN and the height of net opening was 5.62 m. The swept area was 128 m2. The simulated result was close to the experimental result, with maximum relative error less than 20%, and average relative error of 10%. The shape and tension distribution of the trawl and mesh opening performance of the codend were analyzed by numerical simulation. This study could reveal the hydrodynamic performance of the deep bottom trawl for the design and application in the future.